Profitability Ratio of Islamic Rural Banks in Banten Region Post Covid-19 Pandemic - Umami, Khairul; Arfaizar, Januariansyah; Priyo Nugroho, Anton; Nurulhuda Madjamang (Department of Islamic Banking, 2024)
This study evaluates the profitability ratios of Sharia Rural Banks (BPR Syariah) in the Banten region after the Covid-19 pandemic. Profitability is a ratio used by authorities to assess a bank's ability to generate income. The Covid-19 pandemic negatively impacted various economic sectors, including banking, which relies heavily on channeling funds to these sectors. This research uses a quantitative descriptive approach and total sampling, involving the entire population of BPR Syariah in the Banten region, with secondary data sourced from the Financial Services Authority (OJK) for the 2023 period. The study’s results show that the profitability levels of eight Sharia Rural Banks in Banten fall into the adequately sufficient category (average rating of 3). Core earnings remain the primary income source, while non-core earnings also play a significant role. Profitability performance supports capital stability and indicates positive prospects for the future.